Mekanisme, Manfaat, dan Risiko Over Kredit di Indonesia: Analisis Normatif dan Perbandingan Hukum - Ahmad Riadi; Putri Sari Harepa; Siti Jahra Pulungan; Siti Aminah Lubis; Nur Sania Dasopang (Jurnal Bisnis dan Ekonomi Islam, 2025)
This study analyzes the mechanisms, benefits, risks, and mitigation strategies in the practice of over-credit in Indonesia, namely the transfer of credit payment obligations from old debtors to new debtors before the end of the credit period. The phenomenon of over-credit that is rampant is carried out informally resulting in legal uncertainty, financial risks, and ownership disputes, so a comprehensive study based on legal and economic approaches is needed. The research uses normative legal methods by examining laws and regulations, academic literature, research reports, and relevant court decisions. Doctrinal analysis and content analysis are used to examine the suitability between legal norms and field practice, while a limited comparative approach is used to understand credit transfer practices in international jurisdictions. The results of the study show that a legitimate over-credit mechanism requires creditor approval, document verification, assessment of the financial ability of new debtors, and the use of legal agreements through a notary. Over credit provides benefits for existing debtors, new debtors, and creditors, but comes with legal, financial, administrative, and economic risks that increase dramatically when transactions are carried out underhand. Mitigation strategies include creditor involvement, standardization of procedures, document validation, information transparency, and public education. The research concludes that overcredit can be a safe and productive financing instrument if it is carried out in accordance with the provisions of the law and banking prudential standards. Penelitian ini menganalisis mekanisme, manfaat, risiko, dan strategi mitigasi dalam praktik over kredit di Indonesia, yaitu pengalihan kewajiban pembayaran kredit dari debitur lama kepada debitur baru sebelum masa kredit berakhir. Fenomena over kredit yang marak dilakukan secara informal menghasilkan ketidakpastian hukum, risiko finansial, serta sengketa kepemilikan, sehingga diperlukan kajian komprehensif berbasis pendekatan hukum dan ekonomi. Penelitian menggunakan metode hukum normatif dengan mengkaji peraturan perundang-undangan, literatur akademik, laporan penelitian, serta putusan pengadilan yang relevan. Analisis doktrinal dan content analysis digunakan untuk menelaah kesesuaian antara norma hukum dan praktik lapangan, sementara pendekatan komparatif terbatas dipakai untuk memahami praktik pengalihan kredit dalam yurisdiksi internasional. Hasil penelitian menunjukkan bahwa mekanisme over kredit yang sah mensyaratkan persetujuan kreditur, verifikasi dokumen, penilaian kemampuan finansial debitur baru, serta penggunaan perjanjian legal melalui notaris. Over kredit memberikan manfaat bagi debitur lama, debitur baru, dan kreditur, namun disertai risiko hukum, finansial, administratif, dan ekonomi yang meningkat drastis ketika transaksi dilakukan di bawah tangan. Strategi mitigasi meliputi keterlibatan kreditur, standardisasi prosedur, validasi dokumen, transparansi informasi, serta edukasi masyarakat. Penelitian menyimpulkan bahwa over kredit dapat menjadi instrumen pembiayaan yang aman dan produktif apabila dilakukan sesuai ketentuan hukum dan standar prudensial perbankan.